Factors contributing to chondroplasia in degenerate rotator cuff disease - Cornell, HR (2011)
Chondroplasia, the development of cartilage-like characteristics in tendinous tissue, is a form of degeneration found in tendons including those of the rotator cuff. The molecular mechanism of its development is currently unknown. An examination of the features of the torn rotator cuff and the cartilage literature led to the identification of several potential drivers of chondroplasia including cell shape change/actin cytoskeleton and hypoxia. Lovastatin caused actin cytoskeleton disruption and promoted cartilage matrix deposition in the ATDC5 model. It was the most effective member of a panel of cytoskeletal inhibitors, increasing expression of the chondrocytic markers Sox5 and Sox9 and decreasing expression of COL1A1 and COL3A1 in primary human tenocytes. Its effects were dose dependent, reversible by mevalonate addition and long term treatment induced de novo expression of collagen II. Short term hypoxia upregulated VEGF-A and chondrocytic marker gene DEC1 expression but not other chondrocyte markers. Combination treatment with hypoxia did not enhance the effects of lovastatin. These data suggest that modulation of pathways that regulate the actin cytoskeleton and cell shape may alter tenocyte phenotype.